Models for innovation diffusion - Mahajan, Vijay; Peterson, Robert A. (Robert Allen), 1944- (Newbury Park, [Calif.] ; London : SAGE, 1985)
The intellectual environment surrounding diffusion models has been restricted by the language and notation employed in different fields. It's a topic which begs for a sound intellectual introduction. This book provides that introduction, bridging disciplines and setting out findings in a clear and consistent way.
"A SAGE university paper."
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Mathematical models; Diffusion of innovations -- Mathematical models